Partial NSD1 deletions cause 5% of Sotos syndrome and are readily identifiable by multiplex ligation dependent probe amplification. Issue 9 (1st September 2005) - Douglas, J; Tatton-Brown, K; Coleman, K; Guerrero, S; Berg, J; Cole, T R P; FitzPatrick, D; Gillerot, Y; Hughes, H E; Pilz, D; Raymond, F L; Temple, I K; et al.
Abstract : Background: Most cases of Sotos syndrome are caused by intragenic NSD1 mutations or 5q35 microdeletions. It is uncertain whether allelic or genetic heterogeneity underlies the residual cases and it has been proposed that other mechanisms, such as 11p15 defects, might be responsible for Sotos cases without NSD1 mutations or 5q35 microdeletions. Objective: To develop a multiplex ligation dependent probe amplification (MLPA) assay to screen NSD1 for exonic deletions/duplications. Methods: Analysis was undertaken of 18 classic Sotos syndrome cases in which NSD1 mutations and 5q35 microdeletions were excluded. Long range polymerase chain reaction (PCR) was used to characterise the mechanism of generation of the partial NSD1 deletions. Results: Eight unique partial NSD1 deletions were identified: exons 1–2 (n = 4), exons 3–5, exons 9–13, exons 19–21, and exon 22. Using long range PCR six of the deletions were confirmed and the precise breakpoints in five cases characterised. This showed that three had arisen through Alu - Alu recombination and two from non-homologous end joining. Conclusions: MLPA is a robust, inexpensive, simple technique that reliably detects both 5q35 microdeletions and partial NSD1 deletions that together account for ∼15% of Sotos syndrome.